Simultaneous Determination and Quantification of NineNitrosamine Impurities in Semi-Solid Forms Using a GC–MS/MS Method - Namjin Lee; Hyejin Go; Young-joon Park (Separations)
Many studies are being conducted on the detection of nitrosamine impurities in solid formulations. However, research on semi-solid formulations such as gels, ointments and creams is not common. In particular, excipients used to increase viscosity and add fragrance can significantly impact the sample preparation. Volatile compounds derived from natural fragrances are composed of a wide variety of complex components, making them very difficult to handle and completely separate from the analytes. Due to the complex composition of these formulations, an analytical method was developed to accurately separate and analyze nine nitrosamine impurities (NDMA, NDEA, NMEA, NDPA, NDBA, NPIP, NMOR, DIPNA and EIPNA) simultaneously. To overcome challenges in the sample preparation of excipients with physical and chemical properties, the sample was prepared using solvents such as methanol, hexane, water and dichloromethane. The target analytes were extracted with dichloromethane for the final preparation for GC–MS/MS and the optimal conditions were established. While multiple GC columns were tested, peak overlapping interferences were observed, leading to the use of a 60m-long column to overcome peak overlap. The GC–MS/MS condition was set for optimal performance and ionization energy, with parameters adjusted for each analyte. The developed method was validated in accordance with guidelines to ensure its reliability and suitability. As a result, all nine nitrosamine impurities were simultaneously analyzed, confirming excellent performance. The sample preparation method and procedure, column specification and GC–MS/MS conditions have the potential to be adapted not only for semi-solid formulations of pharmaceuticals and cosmetics but also for other formulations such as solid and liquid samples, rendering them suitable for the analysis of nitrosamine impurities.